2013
DOI: 10.1002/grl.50811
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions estimate from airborne measurements over a western United States natural gas field

Abstract: Methane (CH4) emissions from natural gas production are not well quantified and have the potential to offset the climate benefits of natural gas over other fossil fuels. We use atmospheric measurements in a mass balance approach to estimate CH4 emissions of 55 ± 15 × 103 kg h−1 from a natural gas and oil production field in Uintah County, Utah, on 1 day: 3 February 2012. This emission rate corresponds to 6.2%–11.7% (1σ) of average hourly natural gas production in Uintah County in the month of February. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
555
5

Year Published

2014
2014
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 473 publications
(579 citation statements)
references
References 11 publications
(23 reference statements)
19
555
5
Order By: Relevance
“…As an example of variability in emissions between basins, using aircraft measurements, Peischl et al (2015) have reported very different methane emission rates in different natural gas production regions, ranging from a low of 0.18-0.41% of gas production in the northeast Marcellus Shale (Pennsylvania) to rates of 1.0-2.1% in the Haynesville Shale (East Texas) and 1.0-2.8% in the Fayetteville Shale (Arkansas). Using the same type of aircraft-based measurements, emission rates as high as 6.2-11.7% of natural gas production have been reported in the Uintah production region in Utah (Karion et al, 2013). Similarly, Zavala et al (2015a), using measurements of emissions from individual pieces of equipment at hundreds of sites throughout the United States, reported methane emission rates, normalized by rates of natural gas and oil production, that differed by more than an order of magnitude across regions.…”
Section: Spatial Variability In Emissionsmentioning
confidence: 83%
“…As an example of variability in emissions between basins, using aircraft measurements, Peischl et al (2015) have reported very different methane emission rates in different natural gas production regions, ranging from a low of 0.18-0.41% of gas production in the northeast Marcellus Shale (Pennsylvania) to rates of 1.0-2.1% in the Haynesville Shale (East Texas) and 1.0-2.8% in the Fayetteville Shale (Arkansas). Using the same type of aircraft-based measurements, emission rates as high as 6.2-11.7% of natural gas production have been reported in the Uintah production region in Utah (Karion et al, 2013). Similarly, Zavala et al (2015a), using measurements of emissions from individual pieces of equipment at hundreds of sites throughout the United States, reported methane emission rates, normalized by rates of natural gas and oil production, that differed by more than an order of magnitude across regions.…”
Section: Spatial Variability In Emissionsmentioning
confidence: 83%
“…Indeed, the practice of high-volume hydraulic fracturing (fracking) for oil and gas extraction is a growing sector of methane and other hydrocarbon production, especially in the US. Most recent studies M. Saunois et al: The global methane budget 2000709 al., 2014Olivier and Janssens-Maenhout, 2014;Jackson et al, 2014b;Howarth et al, 2011;Pétron et al, 2014;Karion et al, 2013) albeit not all Cathles et al, 2012;Peischl et al, 2015) suggest that methane emissions are underestimated by inventories and agencies, including the USEPA. For instance, emissions in the Barnett Shale region of Texas from both bottom-up and top-down measurements showed that methane emissions from upstream oil and gas infrastructure were 90 % larger than estimates based on the USEPA's inventory and corresponded to 1.5 % of natural gas production (Zavala-Araiza et al, 2015).…”
Section: Shale Gasmentioning
confidence: 99%
“…These studies also identified three possible mechanisms for explaining this relationship, and concluded that the most likely of these is subsurface migration from leaking gas wells. Other researchers have observed thermogenic and other subsurface-sourced methane in atmospheric concentrations high above background levels near conventional and unconventional gas development (4)(5)(6), suggesting that leaking wells may also contribute to fugitive methane and other associated gas emissions, with clear climatic and air quality consequences (7).…”
mentioning
confidence: 99%